First record of the nudibranch Marionia blainvillea (Risso, 1818) (Gastropoda: Heterobranchia) for Montenegro - Mačić, Vesna; Jovanović, Milica; Trkov, Domen; Lipej, Lovrenc (2018)
One specimen belonging to the nudibranch Marionia blainvillea (Risso, 1818) was found crawling on the gorgonian Leptogorgia sarmentosa (Esper, 1789) at Sv. Nedjelja, Boka Kotorska Bay, Montenegro. This is the first record of the species for Montenegrin waters and the third for the Adriatic Sea.
Jedan primjerak puža golaća Marionia blainvillea (Risso, 1818) nađen je da puzi na gorgoniji Leptogorgia sarmentosa (Esper, 1789) na lokaciji Sv. Nedjelja, Bokokotorski zaliv, Crna Gora. Ovo je prvi nalaz te vrste za Crnu Goru i treći za Jadransko more.
Bibliografija: str. 151-152.
Summary ; Sažetak.
Keywords: Marionia blainvillea -- Puž golać -- Koraligenska zajednica; Boka Kotorska -- Crna Gora